Peran Media Sosial dalam COVID-19 - Nova Primadina (PROCEEDING UMSURABAYA, 2023)
AbstractThis pandemic has been going on for almost 2 years and all sectors of life have been significantly affected by this COVID-19 pandemic. The impacts are most pronounced in the health, economic and education sectors. This increase in the use of social media is in line with the restrictions on community activities during the COVID-19 coronavirus pandemic. Various activities of working, studying, and shopping are mostly done by utilizing digital technology from home.Â Keywords: Media, COVID-19, Digital